IDENTIFIKASI SENYAWA ANTIBAKTERI PADA DAUN KECAPI (Sandoricum koetjape (Burm.f.) - I M. Dira Swantara; Yenni Ciawi (Jurnal Kimia (Journal of Chemistry), 2009)
Identification of antibacterial compound for Micrococcus luteus dan Eschericia coli bacteri have beenconducted to kecapi leaf extract (Sandoricum koetjape (Burm.f.)). Extraction of that compounds was carried out bymaseration methods using 70% etanol. Separation of the fraction by liquid-liquid partition (n-hexane, ethyl acetateand chloroform) and two step column chromatographic method using silicagel as stationary phase and ethyl acetate –chloroform (3:7;2,5:7,5; dan 2:8) as first eluent and ethyl acetate – chloroform (2:8; 1,5:8,5; dan 1:9) as secondeluent. The active fraction (2.1 and 2.3 fraction) were identified by gas chromatography-mass spectroscopy (GCMS).The 2.1 fraction contain 3 compound which are heksil n-valerate (C11H22O2); 2,3-dihidrobenzofurane (C8H8O);and 2,6-dimetoxy fenol (C8H10O3). The 2.3 fraction contain 2 compound which are ester dioctilehexadioat(C22H42O4) with M+ = 370 and basic peak equal to 129 and 3,5-di-tert-buthyl-4-hydroxy-toluene (C15H24O).